Venous thromboembolic screening in pediatric trauma: A prospective cohort study of risk-stratified ultrasonography. Issue 1 (26th January 2023) - Tobias, Joseph; Labuz, Daniel F.; Cunningham, Aaron; Dixon, Alexandra; Selesner, Leigh; Moss, Lori; Dewey, Elizabeth; Haley, Kristina M.; Burns, Erin; Schreiber, Martin; Wilson, Rachel; Hamilton, Nicholas A.; et al.
Abstract : This prospective observational cohort study evaluates risk-stratified VTE screening in severely injured children and demonstrates a significant incidence of previously unrecognized, asymptomatic VTE. Abstract : BACKGROUND: This prospective observational cohort study evaluates risk-stratified venous thromboembolism (VTE) screening in injured children. While the reported incidence of VTE is 6% to 10% among critically injured children, there is no standard for screening. Venous thromboembolism may have long-term sequelae in children, including postthrombotic syndrome. METHODS: Patients admitted to a level 1 pediatric trauma center were risk stratified for VTE using a validated prediction algorithm. Children at high risk (risk scores ≥523; i.e., ≥1% risk) received screening duplex ultrasonography. Children at moderate risk (risk scores 410–522; i.e., 0.3–0.99% risk) were screened as a comparison/control. RESULTS: Three-hundred fifty-five children were consecutively risk stratified from October 2019 to May 2021. Forty-seven children received screening duplex ultrasounds: 21 from a high-risk cohort and 26 from a moderate-risk cohort. Four children were diagnosed with VTE in the high-risk cohort compared with seven in the moderate-risk cohort ( p = 0.53). Total incidence of VTE among screened children was 23.4% (11 of 47). Asymptomatic VTE accounted for 81.8% of all events (9 of 11). Fifty-four percent (6 of 11) of VTE were central venous catheter associated. Venous thromboembolism in surviving children resolved by 3 to 6 months with no symptoms of postthrombotic syndrome after 1 year. No cases of VTE were identified in unscreened children, yielding an institutional VTE incidence of 3.1% (11 of 355). DISCUSSION: Risk-stratified screening demonstrates a significant incidence of asymptomatic VTE in injured children. These results may guide reevaluation of prediction algorithms developed from symptomatic VTE risk and longitudinal study of the sequelae of asymptomatic VTE. LEVEL OF EVIDENCE: Prognostic and Epidemiological; Level III. Abstract :